2012
DOI: 10.1002/jmv.23316
|View full text |Cite
|
Sign up to set email alerts
|

p53 and Sp1 cooperate to regulate the expression of epstein–barr viral Zta protein

Abstract: Epstein–Barr virus (EBV) belongs to the gammaherpesvirus family. To produce infectious progeny, EBV reactivates from latency into the lytic cycle by expressing the determinative lytic transactivator, Zta. In the presence of histone deacetylase inhibitor (HDACi), p53 is a prerequisite for the initiation of the EBV lytic cycle by facilitating the expression of Zta. In this study, a serial mutational analysis of Zta promoter (Zp) indicated an important role for the ZID element in responding to HDACi induction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
(76 reference statements)
1
21
0
Order By: Relevance
“…Our group and others have shown that p53 is important for EBV lytic reactivation in many cell lines (13,17,38), and p53 has been reported to form a complex with SP1 that binds to, and activates, the Z promoter (17). In addition, p53 was recently shown to inhibit expression of the ZEB-1 and ZEB-2 proteins (49), which are potent repressors of the Z promoter (24), by inducing expression of microRNAs that degrade ZEB-1/-2.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our group and others have shown that p53 is important for EBV lytic reactivation in many cell lines (13,17,38), and p53 has been reported to form a complex with SP1 that binds to, and activates, the Z promoter (17). In addition, p53 was recently shown to inhibit expression of the ZEB-1 and ZEB-2 proteins (49), which are potent repressors of the Z promoter (24), by inducing expression of microRNAs that degrade ZEB-1/-2.…”
Section: Discussionmentioning
confidence: 92%
“…Since we recently showed that the tumor suppressor protein p53 greatly facilitates lytic reactivation induced by overexpression of the EBV Na (BRRF1) and R proteins (38), and DNA damage potently activates p53 transcriptional function (84,86), DNAdamaging agents could potentially induce EBV reactivation (at least partially) via activation of p53. Recently, p53 was also shown to be required for HDACi-mediated lytic reactivation in both EBV-positive nasopharyngeal carcinoma cell lines and lymphoblastoid B cell lines (13,17,38), further confirming a critical role of p53 function in controlling EBV reactivation in a variety of different settings.…”
mentioning
confidence: 81%
“…Sp1 has been characterized as a bona fide transcription activator of the Z promoter and the R promoter (49,58). Recent studies have suggested that Sp1 cooperates with protein kinase C␦ (PKC␦) and p53 to regulate Z promoter activity (49,50). Sp1 and ZBP-89 also interact directly with the viral replication proteins EA-D and BALF5 (17).…”
Section: Discussionmentioning
confidence: 99%
“…6A and B). Sp1 may also play a direct role in regulating early lytic genes required for EBV lytic infection, as evidenced by the presence of the Sp1 DNA binding element in the promoters of lytic genes (48,50,60,64,65). However, the role of Sp1 in localization of EBV replication proteins to replication compartments may not be directly related to its transcriptional activity on early viral lytic genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation